The Influence of Consumer-Based Brands Equity on Brand Loyalty Through Customer Satisfaction - Sudjudi Widia Kurnianingsih; Sri Vandayuli Riorini (PT FORMOSA CENDEKIA GLOBAL, 2021)
The purpose of this study is to analyze the effect of Consumer-based brand equity on Brand loyalty through Customer satisfaction. This study used purposive sampling data collection techniques. This study was analyzed using the Structural Equation Model (SEM) analysis method. The results of this study indicate (1) The Influence Dimensions of Consumer-Based Brand Equity on Customer Satisfaction, where (1a) Perceived quality has no positive effect on Customer satisfaction; (1b) the Perceived value of cost has a positive effect on Customer satisfaction; (1c) Brand identification has no positive effect on Customer satisfaction; (1d) Trust has a positive effect on Customer satisfaction; (1e) Lifestyle congruence has a positive effect on Customer satisfaction. (2) Customer satisfaction has a positive effect on Brand loyalty. (3) The Influence Dimensions of Consumer-Based Brand Equity on Brand loyalty through Customer Satisfaction, where (3a) Customer satisfaction mediates the influence of Perceived quality on Brand loyalty in full; (3b) Customer satisfaction mediates the influence of Perceived value of cost on Brand loyalty in partial; (3c) Customer satisfaction mediates the influence of Brand identification on Brand loyalty in partial; (3d) Customer satisfaction mediates the influence of Trust on Brand loyalty in full; (3e) Customer satisfaction mediates the influence of Perceived quality on Brand loyalty in partial. The advice for further researchers can conduct research on various types of other food and beverage businesses, such as restaurant, bakeries, and cafes.